Recent developments in vaccination against malaria: Nor-MDP, saponin, corynebacteria, and pertussis organisms as immunological adjuvants in experimental malaria vaccination of macaques - Mitchell, G. H. (1979)
Vaccination of primates against malaria using antigen derived from erythrocytic parasite stages has been most successful where Freund's complete adjuvant has been employed. Since this adjuvant is clinically unacceptable its replacement is a matter of urgency. In the present work a muramyldipeptide derivative (nor-MDP) given in mineral oil has proved to be partially effective as an adjuvant for merozoite vaccination of Macaca mulatta against Plasmodium knowlesi, and saponin has proved to be effective in similar vaccination of M. fascicularis.